ANALYSIS OF RICE FARMERS’ PERCEPTION AND ADAPTATION STRATEGIES TO CLIMATE CHANGE IN BAUCHI AND JIGAWA STATES, NIGERIA - Zakari, A.; Garba, M.; Hamidu, B.; Garba, A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study analyzed rice farmers’ perception and adaptation strategies to climate change in Bauchi and Jigawa States, Nigeria. A multi-stage sampling procedure was used to select 400 rice farmers from the study area. Data were collected using structured questionnaires and analyzed using descriptive and inferential statistics. The results showed that, the mean age of the respondents was 44 years in Bauchi and Jigawa States, the result also revealed that most (92.5%) and majority (88.5%) of respondents were male in Bauchi and Jigawa States respectively. Similarly, the results further revealed that most (90.5%) and majority (78.0%) of respondents were married in both States with a mean household of 7 persons. The results also showed that 36.5% and 34.5% of respondents had secondary education in both States with the mean farming experience of 26 years in Bauchi State and 25 years in Jigawa State respectively. Majority of farmers in Bauchi and Jigawa State perceived that climate change has led to increase in temperature with a mean of (=2.4) and (=2.7) respectively. The results also revealed that farmers in Jigawa State perceived that climate change has led increase in rainfall in Jigawa State with a mean of (=2.3) while farmers in Bauchi State perceived decreased in rainfall with a mean of (=1.7). Principal component analysis (PCA) revealed that the three principal components explained approximately (32%) crop management factor, while sustainable resource management and livelihood diversification factor account for (26%) of the variation, soil conservation and management practice factor account for (28%) variation in the sample. It can be concluded that rice farmers in the study area perceived increased in temperature, precipitation, pest and diseases, dry season as the consequences of climate change. The study recommends that government at all levels, non-governmental organizations and other stakeholders should join hands and extend their climate change awareness campaign deep into the rural communities where no attention or less care is given to environmental sustainability.